General Overproduction - Crocker, Uriel H.; Macvane, S. M. (Quarterly Journal of Economics, 1887)
Uriel H. Crocker, S. M. Macvane; General Overproduction, The Quarterly Journal of Economics, Volume 1, Issue 3, 1 April 1887, Pages 362–366, https://doi.or